Analysis of Beginning Reading Ability in Grade 1 Students of Sanggar Guidance Klang Lama Malaysia - Ibliyah, Khusah; Ridwan, M.; Kuswandi, Iwan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
The reading ability of grade 1 students at SB Klang Lama Malaysia is influenced by internal and external factors. Internal factors such as the physiological, intellectual, and psychological of students. Meanwhile, external factors come from family backgrounds and economic factors experienced by students. The purpose of this study is to find out how internal and external factors can affect students' reading ability. In this study, the author uses a qualitative research method with a descriptive research type. The data collection technique uses observation, interviews and documentation. With data analysis techniques using data analysis including data reduction, data presentation, and drawing data conclusions. The results of this study show that students' varying reading ability is highly determined by internal factors and external factors of students.